2018
DOI: 10.1002/lary.27212
|View full text |Cite
|
Sign up to set email alerts
|

The influential factors on the morphological changes of upper airway associated with mouth opening

Abstract: IV. Laryngoscope, 2018.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
21
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 14 publications
(22 citation statements)
references
References 20 publications
1
21
0
Order By: Relevance
“…Lee et al have shown that the upper airway space was reduced with mouth breathing on lateral cephalometry and fiberoptic nasopharyngoscopy 24 . Hu et al demonstrated that the cross‐sectional area of the upper airway, especially the anterior–posterior diameter of the retroglossal space, was significantly decreased with mouth breathing on computed tomography scans, 25 which is in agreement with our study.…”
Section: Discussionsupporting
confidence: 92%
“…Lee et al have shown that the upper airway space was reduced with mouth breathing on lateral cephalometry and fiberoptic nasopharyngoscopy 24 . Hu et al demonstrated that the cross‐sectional area of the upper airway, especially the anterior–posterior diameter of the retroglossal space, was significantly decreased with mouth breathing on computed tomography scans, 25 which is in agreement with our study.…”
Section: Discussionsupporting
confidence: 92%
“…These dramatic differences between the normal and pathological values of the three parameters confirmed the differential-diagnostic role of the acoustic pharyngometry concerning the extent of the pharyngeal dysfunction that underlay the sleep-disordered breathing. The mean cross-sectional areas and airway volumes in any segments assessed by acoustic pharyngometry in 15 OSA patients are statistically significantly smaller in OSA patients than in 15 healthy controls (p<0.05) (7). The minimal cross-sectional area of the upper airway at end-exhalation is measured in upright position and breathing through the mouth in 60 subjects, 35 males and 25 females at a mean age of 42 years (range, 21-81 years) (2).…”
Section: Resultsmentioning
confidence: 83%
“…Ayuse et al [22] reported that mouth breathing increased upper airway collapsibility during midazolam sedation. A study which enrolled 138 OSAS patients proved that mouth breathing resulted in reduction of oropharyngeal lumen by computed tomography scans [23]. It had been reported that oral patches for prevention open mouth breathing are useful to treat mild OSAS [24].…”
Section: Discussionmentioning
confidence: 99%